​​The Frequency of Gangrenous Infarction of Intestine in Patients Undergoing Intestinal Resection at Tertiary Care Hospital, Rawalpindi : Gangrenous Infarction in Patients with Intestinal Resection - Ruqia, Mehak; Waheed, Khizra; Maheen, Maimoona; Nazir, Aamna; Malik, Aqiba; Hameed, Muhammad Sheraz; Haider, Ali; Asghar, Abdullah; Rehman, Abdur; Arshad, Sarah (Pakistan Journal of Health Sciences, 2024)
Gangrenous bowel or dead bowel most often occurs as a result of hernia, adhesions, and mesenteric insufficiency. Intestinal gangrene due to acute mesenteric vascular events requiring surgery is one of the most common surgical emergencies at tertiary care hospitals. Objective: To determine the frequency of gangrenous infarction in patients undergoing intestinal resection at a tertiary care hospital. Methods: This descriptive cross-sectional study was conducted in the Department of Surgery and Pathology, Rawalpindi, Pakistan. A total of 140 resected intestinal specimens were included in this study. Data were entered and analyzed using SPSS v. 23. o. Descriptive statistics were applied and a P-value <0.05 was taken as statistically significant. Results: Out of 140 samples, clinical specimens from 30(21.4%) patients were found to be gangrenous. The frequency of gangrene was slightly higher in females 16 (53.3%) as compared to males 14 (46.7%) with a peak of 19 patients (63.3%) in the age group of 31 to 60 years and mostly affecting the small intestine 21 (70%). Among the total of 110 (78.6%) non-gangrenous specimens; mild inflammatory changes, perforation, ulceration, tumors, mucosal and mural infarction, infection, reactive hyperplasia, and autolytic changes were noted. Conclusions: The frequency of intestinal gangrene is much higher in our population than in most regions of the world, slightly more common in females as compared to males with a peak in the age group of 31 to 60 years and mostly involving the small intestine, indicating negligence towards this important problem.